Seismic Behavior and Design of Wall–EDD–Frame Systems - Lavan, Oren; Abecassis, David (Frontiers in Built Environment, 2015)
Walls and frames have different deflection lines and, depending on the seismic mass they support, may often poses different natural periods. In many cases, wall-frame structures present an advantageous behavior. In these structures the walls and the frames are rigidly connected. Nevertheless, if the walls and the frames were not rigidly connected, an opportunity for an efficient passive control strategy would arise: Connecting the two systems by energy dissipation devices (EDDs) to result in wall-EDD-frame systems. This, depending on the parameters of the system, is expected to lead to an efficient energy dissipation mechanism. This paper studies the seismic behavior of wall-EDD-frame systems in the context of retrofitting existing frame structures. The controlling non-dimensional parameters of such systems are first identified. This is followed by a rigorous and extensive parametric study that reveals the pros and cons of the new system versus wall-frame systems. The effect of the controlling parameters on the behavior of the new system are analyzed and discussed. Finally, tools are given for initial design of such retrofitting schemes. These enable both choosing the most appropriate retrofitting alternative and selecting initial values for its parameters.